A Critical and Comparative Analysis of Teodoro Pérez’s Approaches to Caring and Demo-cratic Coexistence - Forero Baena, Carmen; Guerra Morales, Evelyn (Rastros Rostros, 2015)
This article expresses the Colombian society’s need to achieve coexistence in a caring and democratic way, and the desire to build spaces based on nurturing strategies that promote interaction. These ideas are complemented by the theories, laws and principles of Gestalt, the information processing ideas of Gagné, and the complex thinking of Morin. The aim of this article is to analyze the approaches and positions of Teodoro Pérez in relation to maintaining spaces that are compatible with citizen respect, following a social and human development method. It is concluded that, despite the difficulty of the task, and given its need, man must rediscover and understand himself, live in peace and share his ethos without selfishness